2020
DOI: 10.1080/1359432x.2020.1774557
|View full text |Cite
|
Sign up to set email alerts
|

Between-person and within-person effects of telework: a quasi-field experiment

Abstract: This quasi-experimental study examines the impact of telework on employees' stress, work-tohome conflict, work engagement and job performance on a between-person and a within-person level. Data were collected in a Belgian company that had launched a pilot telework initiative.Employees in the intervention group (N = 39) were allowed to work from home on at most two days a week whereas employees in the control group (N = 39) were not. To examine changes in person-level outcomes over time, we collected data befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 114 publications
7
136
0
4
Order By: Relevance
“…Studies indicated evidence for these benefits; for example, the research in the Greater Dublin Area by Caulfield (2015) found employees saving travel time and value of travel time. Some studies point out that telework can reduce turnover rate and increase employees' productivity, job engagement, and job performance (Collins and Moschler 2009;Delanoeije and Verbruggen 2020). Similarly, e-working can increase productivity, flexibility, job satisfaction, WLB, including reducing work-life conflict and commuting (Grant et al 2019).…”
Section: /11/2020mentioning
confidence: 99%
“…Studies indicated evidence for these benefits; for example, the research in the Greater Dublin Area by Caulfield (2015) found employees saving travel time and value of travel time. Some studies point out that telework can reduce turnover rate and increase employees' productivity, job engagement, and job performance (Collins and Moschler 2009;Delanoeije and Verbruggen 2020). Similarly, e-working can increase productivity, flexibility, job satisfaction, WLB, including reducing work-life conflict and commuting (Grant et al 2019).…”
Section: /11/2020mentioning
confidence: 99%
“…Further, the amount of time people telework is believed to shape the experience and impact of telework. Teleworking more than 2-3 days a week is reported to produce negative health impacts (Gajendran and Harrison 2007), but teleworking up to 2 days a week is linked to higher work engagement and job performance and less stress (Delanoeije and Verbruggen 2020). Similarly, Raišienė et al (2020) found employees who telework for up to 2 days per week express more positive opinions about teleworking than those who telework full time or for the majority of their work week.…”
Section: Health Implications Of Home-based Teleworkingmentioning
confidence: 99%
“…The effects of teleworking may depend on an individual's personal characteristics, with successful teleworkers reported to be independent, confident, comfortable with solitude, have a high-level of job knowledge, good time management, and strong organizational and communication skills (Tavares 2017). Delanoeije and Verbruggen (2020) noted that low self-management ability can increase stress among teleworkers. Job-role characteristics may also influence the experience of teleworking.…”
Section: Health Implications Of Home-based Teleworkingmentioning
confidence: 99%
See 2 more Smart Citations